David Hume e o problema da justificação da resistência ao governo - Stephanie Hamdan Zahreddine (2018)
This research aims to offer a solution to the problem of justification of resistance to government as exposed by David Hume’s political thought. It starts by investigating Hume's concept of resistance to government - which can be basically understood as the cessation of civil obedience - and the problem about its justification, followed by the exam of the solutions offered by the interpretative literature on Hume. After that, the thesis proposes to solve this problem by means of Hume’s principle of custom, allied to the notion of common interest, which are explored by the author since his first work - The Treatise of Human Nature - and also in the Political Essays and in The History of England. Lastly, a study of cases of resistance to government as described by Hume in the History of England is carried out in order to evince the validity of the solution, in which the principle of custom and the common interest are decisive elements for Hume's diagnosis and assesments about the justification or non-justification of cases of resistance to the government. It will be possible to conclude that there is a continuity between the author's works on regard to this question, since the principles and structure of Hume's (political) philosophy of the Treatise are implicitly present in the Political Essays and in the History of England.